Magnet Summary Strategy in Descriptive Writing: The Case of Madrasah Students in South Sumatera - Suparno; Lenny Marzulina; M Zuhri (ELITE Association Indonesia, 2019)
The purpose of this study were to find out whether or not (1) there was a significant improvement on students’ descriptive writing achievement taught by using Magnet Summary Strategy before and after the treatment and (2) there was a significant difference on students’ descriptive writing achievement between the students who were taught by using Magnet Summary Strategy and those who were not. The sample were 68 students taken from 139 of the population. A quasi- experimental method was used in this study. Writing test was used to collect the data. Based on the result of the data analysis by using paired sample t-test, the p-ouput was 0.000 and the t-value was 11.347. It can be stated that there was a significant improvement on students’ descriptive writing between those who were taught by using Magnet Summary strategy and those who were not before and after treatment. Based on the result of independent t-test, the p-ouput was 0.000 and the t-value was 5.994. It could be stated that there was a significant difference on students’ descriptive writing achievement between those who are taught by using Magnet Summary strategy and those who are not. It could be assumed that Magnet Summary strategy could be used as an alternative strategy in teaching descriptive writing.